Feature characterization of scarring and non‐scarring types of alopecia by multiphoton microscopy. Issue 1 (24th September 2018) - Lin, Jessica; Saknite, Inga; Valdebran, Manuel; Balu, Mihaela; Lentsch, Griffin; Williams, Joshua N.; Koenig, Karsten; Tromberg, Bruce J.; Atanaskova Mesinkovska, Natasha
Abstract : Objectives: Non‐invasive visualization of hair follicles is important for proper diagnosis and management of alopecia; however, histological assessment remains the gold standard. Laser imaging technologies have made possible noninvasive in vivo evaluation of skin and hair follicle. The aim of this study was to evaluate the ability of multiphoton microscopy (MPM) to non‐invasively identify morphological features that can distinguish scarring from non‐scarring alopecia. Methods: MPM images were obtained from areas on the scalp affected by alopecia. Investigators blinded to the diagnosis analyzed hair follicle and shaft sizes. Patients were recruited and imaged at the UC Irvine Health Medical Center and the University of California, Irvine Beckman Laser Institute. Patients with androgenetic alopecia (AGA) and alopecia areata (AA), and scarring alopecia, in particular frontal fibrosing alopecia (FFA) were recruited and imaged from July 2016 to July 2017. Results: We imaged 5 normal scalp subjects and 12 patients affected by non‐scarring (7 subjects) and scarring (5 subjects) alopecia. In normal and non‐scarring alopecia patients, MPM identified presence of sebaceous glands associated with hair follicles. MPM images of scarring alopecia were characterized by the presence of inflammatory cells surrounding hair follicles. Measurements of hair follicle diameter sizes were found to be significantly smaller in scarring alopecia patients compared to normal ( P < 0.001) and compared to non‐scarring alopecia patients ( P = 0.046); non‐scarring hair follicles were also significantly smaller than normal hair follicles ( P = 0.043). Conclusions: This study shows that MPM imaging can non‐invasively identify morphological features that distinguish scarring from non‐scarring alopecia. Further studies are needed to validate this technique and evaluate its potential to be used as an aid for guiding treatment. Lasers Surg. Med. 51:95–103, 2019. © 2018 Wiley Periodicals, Inc.